Humeral Aneurysmal Bone Cyst in a Cat with Sequential Computed Tomographic Findings - Kihoon Kim; Hyungjoon Kim; Hyosung Kim; Yeonhea Lee; Jaehwan Kim; Sunhee Do; Hwiyool Kim (Veterinary Sciences, 2022)
A 7-year-old spayed female domestic shorthair cat presented with a swollen right forelimb and mild lameness. On physical examination, the mass was palpable in the right humeral region, and the cat exhibited pain on palpation. Radiography revealed an expansile osteolytic lesion at the proximal end of the right humerus. Computed tomography (CT) revealed an expansile bony mass on the proximal end of the right humerus and a mild periosteal reaction around the acromion of the scapula. Amputation of the right forelimb, including the scapula and removal of the axillary lymph node, were strongly recommended to the owner, but were declined. Four months after the initial presentation, the cat presented with a dramatically swollen right forelimb and progressive lameness. CT was performed again. In addition to osteolytic changes in the mass, vascular development had occurred at the cranioproximal region. The right forelimb, including the scapula and ipsilateral lymph nodes, was removed. The cat died during the postoperative recovery period. Based on clinical, diagnostic imaging, and histological findings, the final diagnosis was aneurysmal bone cyst. To the best of our knowledge, this is the first case of an aneurysmal bone cyst in the humerus of a cat.